The effects of tranylcypromine on osteoclastogenesis in vitro and in vivo. Issue 9 (10th July 2019) - Liu, Zhuochao; Yang, Kai; Yan, Xueming; Wang, Tianqi; Jiang, Tao; Zhou, Qi; Qi, Jin; Qian, Niandong; Zhou, Hanbing; Chen, Bo; Huang, Ping; Guo, Lei; et al.
ABSTRACT: Identification of anti‐osteoclastogenic agents is important for the treatment of bone loss diseases that feature excessive osteoclast (OC) activity and bone resorption. Tranylcypromine (TCP), an irreversible inhibitor of monoamine oxidase (MAO), has been used as an antidepressant and anxiolytic agent in the clinical treatment of mood and anxiety disorders. TCP has been discovered to exert anabolic effect on osteoblasts, and MAO‐A has also been verified as an important mediator in prostate cancer cells to accelerate osteoclastogenesis. In current study, we were focused on TCP and MAO‐A effects on osteoclastogenesis. As illustrated by tartrate‐resistant acid phosphatase staining, TCP was capable of inhibiting osteoclastogenesis induced by receptor activators of the NF‐κB ligand (RANKL) in bone marrow‐derived macrophage cells without any cytotoxicity. It was also shown to effectively suppress bone resorption of OCs. The subsequent study revealed that TCP inhibited osteoclastogenesis‐related genes in a time‐dependent manner through protein kinase B (AKT)–mediated mechanism followed by the nuclear factor of activated T cells, cytoplasmic 1 (NFATc1)‐c‐fos pathway. And TCP could overcome the osteoclastogenic effects of AKT activator SC79. In addition, our results indicated that the expression and catalytic activity of MAO‐A were up‐regulated by RANKL stimulation and down‐regulated by TCP in vitro and in vivo . Furthermore, the effects of MAO‐A knockdown on OC differentiation indicated that MAO‐A played an important role in osteoclastogenesis in vitro and might contribute to the inhibitory effects of TCP. And AKT, NFATc1, and c‐fos were involved in the MAO‐A pathway. Notably, our in vivo study reflected that TCPs were capable of restoring the bone loss in LPS‐induced calvaria osteolysis and estrogen deficiency–induced osteoporosis models. Thus, our current work provided a potential option for the treatment of bone loss diseases and highlighted the important role of MAO‐A in osteoclastogenesis as well.—Liu, Z., Yang, K., Yan, X., Wang, T., Jiang, T., Zhou, Q., Qi, J., Qian, N., Zhou, H., Chen, B., Huang, P., Guo, L., Zhang, X., Xu, X., Jiang, M., Deng, L. The effects of tranylcypromine on osteoclastogenesis in vitro and in vivo . FASEB J. 33, 9828–9841 (2019). www.fasebj.org